Mid-infrared fibre photonics glass materials, fibre fabrication and processing, laser sources and devices - Jackson, Stuart (Woodhead Publishing series in electronic and optical materials., 2021)
Mid-Infrared Fibre Photonics: Glass Materials, Fibre Fabrication and Processing, Laser Sources and Devicess combines the latest glass chemistry, fibre fabrication and post processing techniques to provide a comprehensive reference on the fundamental science and latest research in fibre photonics for the mid-infrared range. The book systematically reviews the key glass materials systems including fluorides, chalcogenides, and oxides. Each materials chapter includes discussion of composition, structure, thermal, optical and mechanical properties, extrinsic and intrinsic loss mechanisms, materials preparation and purification techniques. Then Mid-Infrared Fibre Photonics: Glass Materials, Fibre Fabrication and Processing, Laser Sources and Devicess covers the most relevant fabrication, post-processing, and spectroscopy techniques. Fibre sources are also addressed including fibre sources for continuous wave emission, pulsed emission, and broadband emission. The book concludes with a brief overview of important medical, sensing and defence applications.